2014
DOI: 10.1681/asn.2013040392
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Change in Estimated GFR among Persons with CKD

Abstract: Physical activity may counteract metabolic disturbances that promote the progression of CKD. To address this concept, we performed a longitudinal cohort study of 256 participants in the Seattle Kidney Study, a clinic-based study of CKD. Participants with an estimated GFR (eGFR) of 15-59 ml/min per 1.73 m 2 at baseline were eligible for the study. Physical activity was quantified using the Four-Week Physical Activity History Questionnaire. We used generalized estimating equations to test associations of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 52 publications
8
101
2
6
Order By: Relevance
“…In our data, the patients with higher frequency of attendance to our cardiac rehabilitation program experienced an improvement of renal function as previously reported [15]. A prospective cohort study demonstrated that increasing physical activity delayed the deterioration of renal function in patients with stage G3-G4 CKD [8]. Furthermore, recent study reported that an aerobic exercise program was safely performed by patients with IHD who have CKD and improved their eGFR [15].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our data, the patients with higher frequency of attendance to our cardiac rehabilitation program experienced an improvement of renal function as previously reported [15]. A prospective cohort study demonstrated that increasing physical activity delayed the deterioration of renal function in patients with stage G3-G4 CKD [8]. Furthermore, recent study reported that an aerobic exercise program was safely performed by patients with IHD who have CKD and improved their eGFR [15].…”
Section: Discussionsupporting
confidence: 84%
“…Wannamethee et al also reported that maintaining a physically active lifestyle could decrease the risk of all-cause mortality in patients with IHD [17]. Although it was formerly believed that increasing physical activity worsened renal function in patients with CKD via reduced renal blood flow, recent studies have shown beneficial effects on not only exercise capacity [18,19] but also renal function [8,15]. In our data, the patients with higher frequency of attendance to our cardiac rehabilitation program experienced an improvement of renal function as previously reported [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have demonstrated that individual lifestyle behaviors relating to The data are expressed as the mean ± SD and the number of subjects exercise, physical activity and diet correlate with the renal function. Robinson-Cohen et al [32] observed that each 60-min increment in weekly physical activity was associated with a 0.5 % slower decline of the eGFR per year. Howden et al [33] reported that lifestyle modifications focusing on exercise training in patients with CKD produced improvements in the cardiorespiratory fitness, body composition and cardiac diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 From 2004 to the present, the SKS has recruited 691 patients from nephrology clinics at the Veteran's Administration Puget Sound Health Care System, the Harborview Medical Center, and the University of Washington Medical Center (all in Seattle, WA). Patients were eligible for the SKS if they had any stage of CKD, were at least 18 years old, and were not receiving any form of RRT.…”
Section: Study Populationmentioning
confidence: 99%